The Sunday philosophy club - McCall Smith, Alexander, 1948- (McCall Smith, Alexander, 1948- Isabel Dalhousie series., 2004)
Amateur sleuth Isabel Dalhousie is a philosopher who also uses her training to solve unusual mysteries. Isabel is Editor of the Review of Applied Ethics - which addresses such questions as 'Truth telling in sexual relationships' - and she also hosts The Sunday Philosophers' Club at her house in Edinburgh. In this first book in McCall Smith's new series Isabel investigates how a yong man could have fallen to his death from the top balcony of the Usher Hall. She is aided in this by her beautiful niece, Cat, Hugo, Cat's ex- boyfriend (whose own good looks Isabel is tantalised by) and her strict housekeeper, Grace. Isabel is drawn into the heart of Edinburgh's well-heeled if somewhat shady business community as she sets out to discover the truth.